Economic Effects of Product Liability and Other Litigation Involving the Safety and Effectiveness of Pharmaceuticals - Garber, Steven (RAND Corporation, 2013)
Liability effects on the economic performance of the pharmaceutical industry play a prominent role in the debate about the economic effects of product liability in the United States. The author analyzes incentive effects on company decisions, implications for economic outcomes such as drug safety and effectiveness, and suggests how public policy changes could mitigate liability-based sources of inefficient decisions of pharmaceutical companies.